“Laying the Groundwork”: Concurrent Enrollment Teachers’ Experiences Teaching First-Year Composition Courses at Public High Schools in Georgia - Hann, Marissa Dawn (My University, 2025)
The purpose of this study was to understand how six educators at public high schools in Georgia made sense of their experiences teaching concurrent enrollment (CE) first-year composition (FYC) courses. The conceptual framework of the research was anchored in the concepts of liminality (McWain, 2018; Turner, 1966) and threshold concepts (Adler-Kassner & Wardle, 2016; Meyer & Land, 2005). Methods used were a bricolage of narrative inquiry (Clandinin, 2013; Kim, 2016) with phenomenological components (Seidman, 2013) to capture the rich stories of CE FYC teachers. Data collection included semistructured interviews, classroom observations, and researcher memos. Three interviews were conducted with each collaborator. Data analysis included the creation of narrative profiles for each collaborator as well as in vivo, process, and versus coding. Five themes were developed to highlight the experiences of the CE FYC teachers in the study: (1) experiencing isolation and detachment while seeking support, (2) balancing workload while desiring autonomy, (3) managing complex decisions while dealing with uncertainty, (4) nurturing students while preparing them for the future, and (5) looking backward while pressing forward. The findings of this study supported three pieces of advice to CE partners to strengthen CE partnerships and support CE teachers: (1) foster mutual relationships between high school and college writing faculty, (2) provide meaningful, relevant resources to CE teachers, and (3) consider CE teachers’ workloads. This study added to the literature on CE programs and FYC courses.
Keywords: Dissertations, Academic--United States; Narrative inquiry; Education, Secondary; Public schools; Georgia; Dual enrollment; High schools; High school teachers